Chapter Mortuary Theory, Pottery and Social Complexity at Jebel Moya Cemetery, South-Central Sudan - Chłodnicki, Marek (Poznań Archaeological Museum, 2015)
archaeology - hunter-gatherers - early food producing societies - Northeastern Africa